THE IMPROVEMENT OF BANKING SOFTWARE DEVELOPMENT PROJECT BY USING SIX-SIGMA FRAMEWORK (CASE: OMNI CHANNEL PROJECT AT DANA BANK) - Winardiansah, Reza
Delivering a software product with good quality is a challenging constraint which is usually sacrificed in order to meet other management constraints such as cost, scope and time. SylicaSoft Group is a regional consulting and technology company which focus on delivering software products to the banking and insurance industry. Within the last three years, the overall Gross Profit Margin for Indonesia's projects were below the management target (65%). It was identified that most of the projects were having a poor-quality product issue.